Implementation of the direct method for improving speaking skills at the Al-Amanah Al-Gontory Islamic Boarding school - Muhammad Fachri Fahrezi; Fathur Rohman (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The question underlying this study is the lack of student activity in speaking skills when learning Arabic. Many students find it difficult to understand Arabic pronunciation. However, this has been improved by implementing the direct method of teaching Arabic at the Al-Amanah Al-Gontory Islamic Boarding School, Through this method, students get used to hearing and speaking the Arabic language during lessons, and for this reason, the researcher was interested in choosing this title and research questions for this research: (1) How to apply the direct method to improve speaking skills at the Al-Amanah Al-Gotory Islamic Boarding School in South Tanggerang ? (2) What are the motives and obstacles to applying the direct method to improve speaking skills at the Al-Amanah Al-Gotory Islamic Boarding School in South Tanggerang ? The research methodology is qualitative research with a classroom approach and its type is case study research. Data collection methods are observation, interviews, and documentation. Data analysis methods are: data reduction, data presentation, and investigation. The results of this research can be summarized as follows: 1) Applying the direct method, there are three steps, which are: As for the introductory step, the teacher begins teaching with a short conversation. The chapter is organized according to the use of the Arabic language. Then, in the main activity step, the teacher directs the students to be attentive for that period. He introduces the new vocabulary directly using a teaching tool such as pictures, movement, or other means, and represents his pronunciation, and the students follow the teacher’s pronunciation. Then, at the conclusion, the teacher asks the students about the duration. All of this is done in Arabic, and the mother tongue is not allowed. The teacher provides advice, motivation, and evaluation for the students. 2) One of the direct motivations at the Amanah Islamic Contour Institute is to increase the students' enthusiasm, as they become accustomed to listening to and speaking Arabic. This makes their tongues stiff when speaking. One of the drawbacks of the direct method is its difficulty in applying it in large classes, which leads to a significant loss of time. It requires a skilled and proficient teacher.